Directional liquefaction coupling fractionation of lignocellulosic biomass for platform chemicals. Issue 10 (19th February 2016) - Xu, Junming; Xie, Xinfeng; Wang, Jingxin; Jiang, Jianchun
Abstract : Conventional thermochemical liquefaction of lignocellulosic biomass produces an unpredictable complex mixture of oxygenated products, which creates techno-economic barriers during subsequent upgrading processes. Abstract : Conventional thermochemical liquefaction of lignocellulosic biomass produces an unpredictable complex mixture of oxygenated products, which creates techno-economic barriers during subsequent upgrading processes. The improvement of the quality of liquefied products is a critical step before the valorization of liquefied lignocellulosic biomass. We are introducing a novel "directional liquefaction" process which harnesses stepwise precipitation of hydrophobic compounds from the liquefied products to form two groups of chemicals: monosaccharides (sugar derivatives) and aromatic platforms. As evidenced in the results of the GC-MS analysis, the sugar platform chemicals, which were generated from carbohydrates, contained five-carbon and six-carbon sugar derivatives, with a total purity higher than 93%. The aromatic platform chemicals with different molecular distributions, mainly from the cleavage of the dominant β-O-4, 4-O-5 linkages in lignin, were fractionated stepwise by gradual removal of the solvent. The platform chemicals make it possible to design the final products due to their similar physiochemical properties within each fraction, and have great potential for commercial production of value added liquid fuels and fine chemicals using mild processing conditions. Additionally, we propose the mechanisms based on our investigation on the decomposition pathways during "directional liquefaction" using GC-MS and 2-dimensional NMR analyses. Overall, the potential of a catalytic refining process for integrated valorization of both carbohydrates and lignin parts in lignocellulosic biomass is the basis of our report.